Selection of phase change material for thermal energy storage in solar air conditioning systems - Xu, Haoxin (2018)
The selection of Phase change materials (PCMs) is crucial in the design of Latent Heat Thermal Energy Storage (LHTES) system in solar air conditioning applications. This study performs a systematic selection procedure of PCMs for LHTES in a typical solar air conditioning system. Comprising prescreening, ranking and objective function examination based on multi-criteria decision making (MCDM) tools, this procedure is able to reflect the system goals of LHTES, as well as to take into account designer's subjectivity. Results indicate the proposed approach to be a highly applicable and efficient tool in the LHTES design process.